Electroacoustic performance of alternative listening devices: candidates for individuals with mild to moderate hearing loss? - Pinsonnault-Skvarenina, Alexis; Bonnet, Fabien; Hotton, Mathieu; Nélisse, Hugues; Voix, Jérémie (Canadian Acoustics, 2023)
The past few years have seen a meteoric rise in technological advancements in the hearing health industry. Advances in connectivity, miniaturization and artificial intelligence enable many increasingly sophisticated and diverse features within multifunctional in-ear devices. Such listening devices, often referred to as “hearables”, aim to become real “bionic ears” offering hearing protection, amplification, monitoring and biodetection functionalities. With the recent approval of the "Over the Counter Hearing Aid Act" in the United States and the introduction of “Over The Counter” ("OTC") hearing aids, these devices now have the potential to revolutionize the world of traditional auditory amplification.The aim of this study is to present a research initiative launched within the ÉTS-EERS Industrial Research Chair in In-Ear Technologies (CRITIAS) at the École de technologie supérieure facility. First, we will discuss the relevant literature onhearables and OTC hearing aids, including the limits and challenges of these devices. Then, we will present our methodological approach to evaluate electroacoustic performances and head-related transfer function (HRTF) of differenthearables and OTC devices, with a sample of preliminary results presented. Finally, we will reflect on new research to be carried to further understand the potential ofhearables and OTC hearing aids to improve communication and quality of life of individual with mild to moderate hearing loss.